PENGARUH MARKETING ONLINE DAN KEAKTIFAN KOMUNITAS TERHADAP PENINGKATAN PENJUALAN EMKM BATIK DI JEMBER - Dania Puspitasari; Elok Fitriya (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2018)
This study aims to determine the influence of online marketing and community activeness to increase sales. The data obtained from the results of the distribution of questionnaires on batik craftsmen in the city of Jember. Questionnaires obtained by researchers as much as 15 batik craftsmen in the city of Jember. Based on the results of research proved that partially online marketing effect on increasing panjualan. Meanwhile, the livelihood of the community has no effect on sales increase. This study can also prove that online marketing and community cohectivity simultaneously affect the increasing sales of batik craftsmen in the city of Jember.